THE RELATIONSHIP BETWEEN HEAD POSTURE AND LEVEL OF PHYSICAL ACTIVITY IN OFFICE WORKERS - Veseta, Una; Upeniece, Irena; Onzevs, Oskars; Liepina, Inga; Lice, Ineta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this study was to discover the relationship between head and neck posture and level of physical activity for office workers. In our study, 66 subjects (women 28-49 age old) who work in office longer than one year, sitting would total about 6 hours per 8 hour workday. Exclusion criteria were self-report of previous significant back injury; current neck or upper back pain; or referred pain into the upper extremity (i.e. cervical radiculopathy). Informed consent was obtained from all participants. Physical activity levels were evaluated using the International Physical Activity Questionnaire short form. The head posture and the craniovertebral angle was measured using photogrammetry, Protractor mobile application using iPhone 6s cell phone. The cervical Range of Motion was analyzed using the inclinometer and the Neck Disability Index as an instrument for self-rated disability. The collected data were analyzed using the methods of mathematical statistics. Pearson correlation was used to determine the relationship of level of physical activity with craniovertebral angle and Neck Disability Index. The results showed physical activity level has no correlations at all, a weak correlation to the craniovertebral angle. There is a correlation between all other head posture indicators.